Pengaruh Pendekatan Structured Learning Approach (SLA) Terhadap Pemahaman Konsep IPAS Kelas IV - Fitriana Aula Handayani; Syofnidah Ifriyanti; Ayu Reza Ningrum (Paedagogie, 2026)
This study aims to analyze the effect of the Structured Learning Approach (SLA) on students’ conceptual understanding in science and social learning (IPAS) at the fourth-grade level of elementary school. The research employed a quantitative approach with a quasi-experimental design, specifically a posttest-only control group design. The participants consisted of 38 students divided into an experimental group and a control group. Data were collected using an essay test that had been validated and tested for reliability. Data analysis included prerequisite tests (normality and homogeneity) and hypothesis testing using an independent sample t-test. The results revealed a significant effect of SLA on students’ conceptual understanding, with a significance value of 0.000 (< 0.05). The mean score of the experimental group (83.79) was higher than that of the control group (71.37). These findings indicate that structured, systematic, and activity-based learning effectively enhances students’ conceptual understanding. Theoretically, this study supports constructivist theory and the revised Bloom’s taxonomy by Anderson and Krathwohl. Practically, SLA can serve as an effective alternative instructional strategy to improve the quality of IPAS learning in elementary schools.